Management and Sustainability of BUMDes Businesses Based on Management Functions: Pengelolaan dan Keberlanjutan Usaha BUMDes Berdasarkan Fungsi Manajemen - Haris Nugraha; M. Kasim M; Deandlles Christover; Ahmad Yani (Academia Open, 2025)
General Background: The management of Village-Owned Enterprises (BUMDes) is an important strategy in driving the rural economy in Indonesia, but its sustainability often faces managerial and institutional challenges. Specific Background: In Benua Baru Village, the BUMDes “Maju Bersama” manages business units such as a night market, cassava chips, and livestock feed corn, which contribute to increasing village income but are hindered by communication and coordination problems following a change in management. Knowledge Gap: Empirical research that thoroughly examines BUMDes management based on management function theory, particularly the supporting and inhibiting factors at the village level, remains limited. Aims: This study analyzes the management of BUMDes “Maju Bersama” using Luther Gulick’s framework (POSDCoRB) and identifies factors influencing business sustainability. Results: The findings show that business management has aligned with the village’s potential and provided a positive impact on the local economy (2018–2022), but has experienced stagnation since 2023 due to weak communication and planning. Novelty: This study presents a village-level analysis integrating management theory with local leadership dynamics. Implications: The results highlight the importance of continuous coordination, communication, and managerial capacity to ensure the sustainability of BUMDes as a driver of the rural economy. Highlights: The sustainability of BUMDes greatly depends on communication and coordination after a change in leadership. The application of Luther Gulick’s management function theory is effective in revealing supporting and inhibiting factors. Aligning business activities with the village’s potential and needs is the key to local economic success. Keywords: BUMDes, Management Functions, POSDCoRB, Business Sustainability, Rural Economy